AKTIVITAS FISIK BERPERAN PENTING DALAM KESEGARAN JASMANI MURID SD - Dwi Agustina; Roikhatul Jannah; Naydial Roesdal (Poltekkes Kemenkes Jambi, 2016)
Primary school age children which is the forerunner of the nation's future should receive specialattention, and its potential needs to be developed continuously since the early stage. Nutritional problemsat elementary school children, both the prevalence of malnutrition and over nutrition is still quite high.Physical fitness in school children is also low, but is vital to the child's ability to carry out any physical activity that have an impact on improving performance.The type of research is non-experimental (observational) analytical with cross sectional approach.. Subjects were grade 4-6 SDN Jatirasa III Bekasi. The research was conducted in October s / d inDecember 2014. Data analysis cover; univariate, bivariate with Sommer's test, multivariate logistic regression analysis multinomial.The results showed physical activity respondents mostly mild (52.2%), 65.4% of respondentshave a good nutritional status. None of the respondents have the habit of smoking. Most respondents(78.7%) physical fitness were excellent and good. Both physical activity and nutritional status have contributed to the physical fitness, but physical activity was the most dominant variable with an OR of 3.9,while the nutritional status of only 1.5.